2020
DOI: 10.1002/jbmr.4681
|View full text |Cite
|
Sign up to set email alerts
|

Bone Mineral Density Is Inversely Associated With Mortality in Chronic Kidney Disease Patients: A Meta-Analysis

Abstract: Low bone mineral density (BMD) is suggested to be associated with increased mortality in the general health population, but the relationship in chronic kidney disease (CKD) patients is still unclear. We performed a meta‐analysis to investigate the association of BMD in different sites with risk of all‐cause mortality in CKD patients. We searched PubMed, EMBASE, and Web of Science to identify eligible cohort studies that evaluated the association between BMD at different sites and risk of all‐cause mortality in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…The 2017 KDIGO recommendations state that when evaluating the diagnostic and treatment requirements for osteoporosis in individuals with CKD, testing BMD may be preferred to doing a bone biopsy [ 4 ]. Furthermore, a 2022 meta-analysis showed that lower BMD values were associated with an increased risk of all-cause mortality in patients with CKD [ 5 ]. In patients with CKD, the clinical utility of BMD measurements for assessing bone loss and other related health conditions remains worth investigating due to the presence of various hormonal and metabolic alterations [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…The 2017 KDIGO recommendations state that when evaluating the diagnostic and treatment requirements for osteoporosis in individuals with CKD, testing BMD may be preferred to doing a bone biopsy [ 4 ]. Furthermore, a 2022 meta-analysis showed that lower BMD values were associated with an increased risk of all-cause mortality in patients with CKD [ 5 ]. In patients with CKD, the clinical utility of BMD measurements for assessing bone loss and other related health conditions remains worth investigating due to the presence of various hormonal and metabolic alterations [ 6 ].…”
Section: Introductionmentioning
confidence: 99%